Probabilistic collocation method for evaluation available transfer capability hybrid wind power system - Khalifa, Othman Omran; Khairuddin, Azhar; Alhammi, Abdelwahab I. (Asian Research Publishing Network (ARPN), 2016)
Available Transfer Capability (ATC) computation of power systems including an excessive wind power penetration became a vital issue for system operation and planning due to the uncertainty and fast variation of wind speed. This paper proposes Probabilistic Collocation Method (PCM) for ATC determination with a grid connected hybrid wind power system. The low-order orthogonal polynomials are utilized to generate the approximation of the random variable of interest as the function of uncertainty parameters. The proposed method is a computational effectual solution to specify quite a precise approximation for the given probability distribution (PD) of system response. Consequently the method can significantly lessen the computational time compared to the traditional Monte Carlo (MC) approach. Examples are given on the IEEE 39 bus system to illustrate the effectiveness of the proposed method.